A mixed methods study to evaluate the effects of a teamwork enhancement and quality improvement initiative on nurses’ work environment - Paguio, Jenniffer Torralba; Yu, Doris Sau Fung (Journal of advanced nursing, 2020)
Aims To test the effect of a teamwork enhancement and quality improvement program named ‘Nurturing Effective Teams and Continuous Quality Improvement’ on nurses’ work environments in the hospital setting. Design Mixed‐method study with quasi‐experimental controlled trial and focus group interviews. Methods Twelve units from two Philippine tertiary government hospitals will be matched and allocated to have 72 nurses receiving the teamwork enhancement and quality improvement program, or no intervention. The program focuses on enhancing the nurse autonomy, leadership and management support, teamwork, and workload management, delivered in two phases: (a) teamwork enhancement training using team strategies and tools to enhance the performance and patient safety; and (b) implementation of quality improvement projects using the model for improvement to identify priority unit issues and change ideas and tested using the Plan‐Do‐Study‐Act cycle. The 6‐month implementation includes two trainings and seven mentoring sessions with a quality improvement facilitator. Primary outcome is the nurses’ work environment and secondary outcomes are job satisfaction, burnout risk, turnover intention, and perceived quality of care provided measured at the nurse‐level using self‐administered survey and measured at 0, 3, and 6 months. Focus group interviews will be conducted among 14–16 nurse subjects to explore their experience during the program, while other stakeholders will be interviewed to reflect the program effects. Generalized equation modelling will be used to identify the program effects on the quantitative outcomes and content analysis will be used for qualitative data. Discussion Establishing measures to improve the nurses’ work environments can be used to address poor nurse outcomes in high workload and low‐resource settings. Impact A favourable nurse work environment is the cornerstone to sustainable nursing workforce and positive outcomes. This study will provide explicit evidence to inform the effect of a structured evidence‐based protocol in improving nurses’ work environment given resource‐limited context. Trial Registration: China Clinical Trial Registration Center (CciCTR), Registration number ChiCTR1900021754 (March 8, 2019). 目的 在医院环境下,探讨‘培育高效团队及持续提高素质’的增强团队合作与素质提高计划对护士工作环境的影响。 设计 准实验对照试验与焦点小组访谈相结合的混合方法研究。 方法 将对来自菲律宾两所三级公立医院的12个单位进行将进行匹配和分配,让72名护士接受增强团队合作与素质提高计划,或不进行干预。该计划的重点是加强护士的自主性、领导力和管理支持、团队合作和工作量管理,分两个阶段进行:(a)使用团队战略和工具进行增强团队合作培训,从而提高护士的表现和患者安全;(b)实施素质提高项目,使用素质提高模型确定优先单元问题和变更思路,并进行计划‐执行‐研究‐行动周期测试。此项目为期六个月,包括两次培训和七次的指导课程,以及一个素质提高指导老师。主要结果是护士的工作环境,次要结果是工作满意度、职业倦怠风险、离职倾向和感知护理质量,采用自我管理式调查在护士中进行测量,并在0、3和6个月进行测量。焦点小组访谈将在14‐16名护士受试者中进行,探索他们在项目期间的经验,而其他利益相关者将接受访谈以反映项目的效果。广义方程模型将用于确定项目对定量结果的影响,内容分析将用于定性数据。 讨论 制定改善护士工作环境的措施,可以解决高工作量、低资源环境下护士工作效果差的问题。 影响 良好的护士工作环境是可持续护理队伍和积极成果的基石。本研究将提供明确的证据,证明在资源有限的情况下架构式循证协议对改善护士工作环境的效果。 试验注册 中国临床试验注册中心(CciCTR),注册号:ChiCTR1900021754(2019年3月8日)